Penyalahgunaan Kewenangan dalam Penetapan Kebijakan Proyek Strategis sebagai Tindak Pidana Korupsi - Muhamad Radjhu Khan Saputra; Audry Salsabila Pasaribu; Ahmad Hamdani; Muhamad Rifki Nurrasman; Margo Hadi Pura; Wiwin Triyunarti (Science and Education Journal (SICEDU), 2026)
This study examines abuse of authority in the determination of strategic project policies as a corruption offense. The central issue concerns the boundary between legitimate governmental policy, administrative error, and abuse of authority that satisfies criminal elements. This research uses normative juridical method with statutory and conceptual approaches. The findings show that the strategic status of a project does not remove the obligation of officials to act under legality, good governance principles, transparency, and accountability. The alleged corruption in the Cirebon-Semarang/Cisem gas pipeline project is positioned as an illustration of supervisory vulnerability, not as proof of corruption, because no court decision exists. Criminal liability may arise only when office, distorted use of authority, benefit for certain parties, state financial loss, and culpability are proven as an integrated chain. This construction is necessary to prevent criminal law from becoming a tool for criminalizing policy while maintaining accountability in national strategic development.